Promoting micro irrigation in India: a review of evidence and recent developments - Verma, Shilp (2004)
In the classical model of irrigation efficiency, all water applied to the crop is treated as consumed or lost while the integrated basin view of irrigation efficiency views only the effective evapo-transpiration as the consumptive use in irrigation. In either case, increased water efficiency at farm/individual level would not lead to water saving at the system (basin) level unless these higher farm efficiencies are achieved system-wide! Thus, unless the adoption of micro-irrigation is scaled up, it would not make any significant contribution to alleviating the problem of groundwater depletion and in resolving various related issues. Even after more than three decades of promotion by various government and non-government agencies, the spread of micro-irrigation in India is miniscule. The limited growth of micro-irrigation technologies in India can, to a large extent, be explained by the apparent gap between what ha s been marketed and where the demand lies. This paper tries to understand the adoption, spread, impacts, market dynamics and constraints of micro-irrigation technologies through an extensive review of literature and by capturing recent development in the field to derive conclusions and implications for promotion of these technologies, especially among the poor.